A new genus for Habrothrix angustidens and Akodon serrensis (RODENTIA, CRICETIDAE): again paleontology meets neontology in the legacy of Lund - Pardiñas, Ulises Francisco J. (2016)
We describe a new genus of sigmodontine rodent to allocate a fossil species from Lagoa Santa cave deposits, Habrothrix angustidens Winge, and a living species from southeastern Atlantic Forest described at the start of the past century, Akodon serrensis Thos. Tentatively, both forms are considered as synonyms pending a detailed revision of the genus. The new genus belongs to the Akodon Division of the diverse tribe Akodontini where, based on molecular evidence, it is sister to Thaptomys, another forest-dwelling akodontine. The new genus is characterized by a unique combination of morphological traits including tail shorter than head-and-body; manual and pedal digits with short claws; skull robust with pointed rostrum, broad and somewhat flat interorbital region with frontal borders divergent posteriorly, and enlarged braincase without crests; large incisive foramina with expanded palatal process of premaxillary; broad mesopterygoid fossa with anterior margin rounded; alisphenoid strut present; carotid arterial circulation pattern primitive; molars noticeably large in relation to the skull and moderately hypsodont; main molar cusps arranged in opposite pairs; first upper molar without anteromedian flexus; length of third lower molar subequal to those of second lower molar; mandible without distinct capsular process; gall bladder present; stomach unilocular and hemiglandular; 2n = 46 (FN = 46). The new genus is an Atlantic Forest endemic, indicating that the diversity of Akodontini has been overlooked outside of the Andes.